Chemical Constituents of Muehlenbeckia tamnifolia (Kunth) Meisn (Polygonaceae) and Its In Vitro ?-Amilase and ?-Glucosidase Inhibitory Activities - Torres, M. (2016)
The phytochemical investigation of Muehlenbeckia tamnifolia, collected in Loja-Ecuador, led to the isolation of nine known compounds identified as: lupeol acetate (1); cis-p-coumaric acid (2); lupeol (3); ?-sitosterol (4) trans-p-coumaric acid (5); linoleic acid (6) (+)-catechin (7); afzelin (8) and quercitrin (9). The structures of the isolated compounds were determined based on analysis of NMR and MS data, as well as comparison with the literature. The hypoglycemic activity of crude extracts and isolated compounds was assessed by the ability to inhibit ?-amylase and ?-glucosidase enzymes. The hexane extract showed weak inhibitory activity on ?-amylase, with an IC50 value of 625 gmL?1, while the other extracts and isolated compounds were inactive at the maximum dose tested. The results on ?-glucosidase showed more favorable effects; the hexanic and methanolic extracts exhibited a strong inhibitory activity with IC50 values of 48.22 gmL?1 and 19.22 gmL?1, respectively. Four of the nine isolated compounds exhibited strong inhibitory activity with IC50 values below 8 M, much higher than acarbose (377 uM). Linoleic acid was the most potent compound (IC50 = 0.42 M) followed by afzelin, (+)-catechin and quercitrin.